PEMAKNAAN PENGGEMAR TERHADAP KODE-KODE FEMININ PADA VIDEO KLIP JKT48 - Nur Fauzi, Fikrii; Dwiningtyas Sulistyani, Hapsari; Nugroho, Adi (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2024)
This study investigates JKT48 fans' reception of feminine codes in a music video, using John Fiske's semiotic analysis and Ien Ang's reception theory. The research offers insights into how fans interpret media texts. Four feminine codes, based on Angela McRobbie's framework, are identified: romance, domestic life, fashion and beauty, and the pop star persona. The romance code depicts women concealing relationships, while the domestic life code portrays them as passive partners. The fashion and beauty code highlights sexualized appearances, and the pop star code presents JKT48 members as glamorous figures. Fan interpretations vary according to their background, knowledge, and media exposure, with some seeing gestures as seductive, while others perceive them as familial. Same-sex relationships are viewed through a heteronormative lens, with fans identifying dominant-passive roles. Future research could adopt a positivist paradigm to examine the broader influence of JKT48 content on regional fandom's attitudes and behaviors.